The theory of kinetic processes in anisotropic phonon systems - Adamenko, I.N.; Kitsenko, Y.A.; Nemchenko, K.E.; Wyatt, A.F.G. (Вопросы атомной науки и техники, 2001)
We present a theoretical investigation of the kinetic properties of strongly anisotropic phonon systems. Such systems can be created in superfluid helium by heat pulses. The general expression for the rates of four-phonon processes are obtained. This expression shows that there is an asymmetry between the creation and decay of the high-energy phonons in the anisotropic phonon systems. Solutions of this expression are then considered. The results presented in this work explain the phenomena which are observed in the anisotropic phonon systems and they will stimulate the conception of new experiments.